Relationship of Biosocial Factors and Hemoglobin Genotype with Age of Menarche among School Girls in Ilorin, Nigeria - Adebara, IO; Ijaiya, Munir'deen A (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: Menarche is an important milestone that signals the commencement of the reproductive life of the growing girl-child. The objectives of the study was to determine the age of menarche among the school girls, the relationship between age of menarche and anthropometric measurements, haemoglobin genotype, sporting activities and age of menarche of respondents’ mothers. Methods: This was a cross-sectional study carried out among selected secondary school students in Ilorin, Nigeria, between September 2008 and April 2009. Multistage and systematic random sampling techniques were used for subjects’ selection. Results: The mean menarcheal age of the respondents was 13.21 ± 1.29years while their mothers’ mean menarcheal age was 14.39± 1.82 years. Girls whose mothers have high level of education and of high social class attained menarche earlier than their other colleagues. The girls’ height, weight and body mass index had no significant influence on the age of menarche. The mean menarcheal age of girls with haemoglobin AA (13.25years) was lower than those with haemoglobin AS (13.79years) and haemoglobin SS (14.17years). The socioeconomic class was however, the only index that was significant on multivariate analysis. Conclusions: Girls are attaining reproductive capacity at a younger age and socioeconomic class was the most important variable that had relationship with age of menarche. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 19-24 DOI: http://dx.doi.org/10.3126/njog.v7i1.8828